Gel polymer electrolyte, preparation method thereof and battery

By using specific matrix polymers and modified polymers in gel polymer electrolytes, the problem of poor interface stability of existing electrolytes is solved, and better battery cycle stability and safety is achieved.

CN119920966APending Publication Date: 2025-05-02CHINA PETROLEUM & CHEMICAL CORP +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311432315.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-31
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

The interface stability of existing gel polymer electrolytes is not ideal and is susceptible to erosion and damage by electrolyte, which affects the cycle stability and safety of the battery.

Method used

A gel polymer electrolyte is provided whose polymer body contains a matrix polymer and a modified polymer, and the interface stability and cyclic stability of the electrolyte are improved by the molar ratio of specific structural units A and structural units B, as well as the selection of modified polymers.

Benefits of technology

The interface between the gel polymer electrolyte and the positive and negative electrode materials of the battery has good stability and high corrosion resistance. It can effectively resist the corrosion damage of the electrolyte and improve the cycle stability and safety of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119920966A_ABST
    Figure CN119920966A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of polymer and electrochemical energy storage, and discloses a gel polymer electrolyte, a preparation method thereof and a battery. The gel polymer electrolyte comprises a polymer main body and an electrolyte salt solution impregnated in the polymer main body, the polymer main body contains a matrix polymer and a modified polymer; wherein the matrix polymer contains a structural unit A as shown in a formula (I) # imgabs 0 # and a structural unit B as shown in a formula (II) # imgabs 1 #; the molar ratio of the structural unit A to the structural unit B is 1: (0.05-28). The gel polymer electrolyte has excellent interface stability, and when the gel polymer electrolyte is used for assembling energy storage devices such as batteries, better cycling stability and safety can be brought.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of polymer and electrochemical energy storage, and in particular to a gel polymer electrolyte and a preparation method thereof and a battery. Background Art

[0002] Semi-solid gel polymer electrolytes have both the high ionic conductivity of liquid electrolytes and the high safety of solid electrolytes, and are highly plastic and compatible with electrodes. However, there are currently few available materials for gel polymer electrolytes, and they are relatively expensive, and their interfacial compatibility with the negative electrode of the battery is not ideal. There is an urgent need to develop gel polymer electrolytes with good interfacial stability. Summary of the invention

[0003] Aiming at the problem that the existing gel polymer electrolyte has unsatisfactory interface stability and is easily corroded and damaged by the electrolyte, thus affecting the cycle stability and safety of the battery, the present invention provides a gel polymer electrolyte and a preparation method thereof and a battery.

[0004] In order to achieve the above-mentioned object, the present invention provides a gel polymer electrolyte in a first aspect, comprising: a polymer body, and an electrolyte salt solution impregnated in the polymer body; the polymer body contains a matrix polymer and a modified polymer;

[0005] Wherein, the base polymer contains a structural unit A represented by formula (I) and a structural unit B represented by formula (II);

[0006]

[0007] In formula (I), R1 and R2 are each independently selected from hydrogen or a C1-C3 alkyl group; R3 and R4 are each independently selected from a C1-C3 alkyl group;

[0008] In formula (II), R5, R6, and R7 are each independently selected from hydrogen or a C1-C3 alkyl group;

[0009] The molar ratio of structural unit A:structural unit B is 1:(0.05-28).

[0010] A second aspect of the present invention provides a method for preparing a gel polymer electrolyte, comprising:

[0011] (1) polymerizing monomer A' and monomer B' to obtain a matrix polymer;

[0012] (2) blending the base polymer and the modified polymer to form a film to obtain a polymer film;

[0013] (3) plasticizing and swelling the polymer film with an electrolyte salt solution to obtain a gel polymer electrolyte;

[0014] Wherein, the monomer A' has a structure shown in formula (III), and the monomer B' has a structural unit shown in formula (IV);

[0015]

[0016] In formula (III), R1' and R2' are each independently selected from hydrogen or a C1-C3 alkyl group; R3' and R4' are each independently selected from a C1-C3 alkyl group;

[0017] In formula (IV), R5', R6', and R7' are each independently selected from hydrogen or a C1-C3 alkyl group;

[0018] The molar ratio of the monomer A':monomer B' is 1:(0.05-28).

[0019] The third aspect of the present invention provides a gel polymer electrolyte prepared by the method described in the second aspect.

[0020] A fourth aspect of the present invention provides a battery comprising the gel polymer electrolyte described in the second or third aspect.

[0021] Through the above technical solution, the gel polymer electrolyte provided by the present invention has good interface stability and corrosion resistance with the positive and negative electrode materials in the battery, can be matched with common electrode materials, and has a long service life. The use of the gel polymer electrolyte to assemble batteries and other energy storage devices can bring better cycle stability and safety. Specifically, the use of the gel polymer electrolyte can make lithium-ion batteries less prone to short circuits during long-term operation. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] The accompanying drawings are used to provide a further understanding of the present invention and constitute a part of the specification. Together with the following specific embodiments, they are used to explain the present invention but do not constitute a limitation of the present invention. In the accompanying drawings:

[0023] Figure 1 This is the infrared spectrum of the matrix polymer in Example 1 of the present invention. DETAILED DESCRIPTION

[0024] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0025] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.

[0026] In a first aspect, the present invention provides a gel polymer electrolyte, comprising: a polymer body, and an electrolyte salt solution impregnated in the polymer body; the polymer body contains a matrix polymer and a modified polymer;

[0027] Wherein, the base polymer contains a structural unit A represented by formula (I) and a structural unit B represented by formula (II);

[0028]

[0029] In formula (I), R1 and R2 are each independently selected from hydrogen or a C1-C3 alkyl group; R3 and R4 are each independently selected from a C1-C3 alkyl group;

[0030] In formula (II), R5, R6, and R7 are each independently selected from hydrogen or a C1-C3 alkyl group;

[0031] The molar ratio of structural unit A:structural unit B is 1:(0.05-28).

[0032] According to the present invention, in the structural units A and B contained in the base polymer, preferably, R1 and R2 are each independently selected from hydrogen or methyl; R3 and R4 are each independently selected from C1-C2 alkyl; R5, R6, and R7 are each independently selected from hydrogen or methyl.

[0033] According to the present invention, in the matrix polymer of the gel polymer electrolyte, the structural unit A and the structural unit B, on the basis of satisfying the above-mentioned proportional relationship, preferably, the molar ratio of the structural unit A:structural unit B is 1:(1-2), which can make the gel polymer electrolyte have better interface stability and cycle stability.

[0034] According to the present invention, in the gel polymer electrolyte, the matrix polymer and the modified polymer contained in the polymer body are physically blended. Preferably, the weight ratio of the matrix polymer: the modified polymer is 1: (0.01-9), which can make the polymer body have a more stable structure. Further preferably, the weight ratio of the matrix polymer: the modified polymer is 1: (1-2).

[0035] According to the present invention, the modified polymer can improve the film-forming property, thermal stability, mechanical properties, liquid absorption capacity, and ionic conductivity of the polymer body. Preferably, the modified polymer can be selected from at least one of polyolefins, polysulfonates, polycarbonates, polyacrylates, polyterephthalates, polyethers, polyimides, polyacrylonitrile, nylon, and cellulose.

[0036] According to a preferred embodiment of the present invention, the modified polymer is selected from at least one of polyolefin, polyacrylate and polyimide, more preferably polyolefin, which can make the gel polymer electrolyte have better interface stability.

[0037] According to the present invention, the polymer body of the gel polymer electrolyte can be a non-porous structure or a porous structure, preferably a porous structure. Preferably, the pores contained in the polymer body have a pore size of 0.1-5 μm and a porosity of 10-80%, so that the gel polymer electrolyte has better interface stability and cycle stability.

[0038] In the present invention, the pore diameters of the pores contained in the polymer matrix are measured by scanning electron microscopy (SEM), and the porosity of the polymer matrix is ​​measured by mass method.

[0039] According to the present invention, in the gel polymer electrolyte, the electrolyte salt solution is impregnated in the polymer body as an electrolyte. The present invention has a wide range of electrolyte salt types in the electrolyte salt solution, and conventional selections in the art can be used, including but not limited to at least one of zinc salts, lithium salts, sodium salts, potassium salts, calcium salts, magnesium salts and aluminum salts. For example, the electrolyte salt can be lithium hexafluorophosphate (LiPF6), lithium bistrifluoromethanesulfonyl imide (LiTFSI) or lithium bisfluorosulfonyl imide (LIFSI), etc.

[0040] In the present invention, the type of solvent in the electrolyte salt solution is relatively broad, and conventional choices in the art can be used, including but not limited to water, carbonates, ethers, ionic liquids, etc. Preferably, the concentration of the salt (the salt refers to a metal ion compound) in the electrolyte salt solution is 0.1-50 mol / L.

[0041] The gel polymer electrolyte provided by the present invention has excellent interface stability, can effectively resist the corrosion and damage of the electrolyte, has high room temperature ionic conductivity, and can be used in a variety of electrochemical energy storage systems, including but not limited to batteries (including secondary batteries), supercapacitors, etc., and can bring better cycle stability and safety to the electrochemical energy storage system.

[0042] According to a most preferred embodiment of the present invention, in the gel polymer electrolyte, the matrix polymer contains a structural unit and structural units Structural unit Structural unit The molar ratio is 1:(1-2), which has further improved interface stability and can make the battery have better cycle stability.

[0043] A second aspect of the present invention provides a method for preparing a gel polymer electrolyte, comprising:

[0044] (1) polymerizing monomer A' and monomer B' to obtain a matrix polymer;

[0045] (2) blending the base polymer and the modified polymer to form a film to obtain a polymer film;

[0046] (3) plasticizing and swelling the polymer film with an electrolyte salt solution to obtain a gel polymer electrolyte;

[0047] Wherein, the monomer A' has a structure shown in formula (III), and the monomer B' has a structural unit shown in formula (IV);

[0048]

[0049] In formula (III), R1' and R2' are each independently selected from hydrogen or a C1-C3 alkyl group; R3' and R4' are each independently selected from a C1-C3 alkyl group;

[0050] In formula (IV), R5', R6', and R7' are each independently selected from hydrogen or a C1-C3 alkyl group;

[0051] The molar ratio of the monomer A':monomer B' is 1:(0.05-28).

[0052] According to the present invention, in step (1), by subjecting the monomers A' and B' to a free radical polymerization reaction in the presence of an initiator, the gel polymer electrolyte finally obtained can have excellent interface stability.

[0053] According to the present invention, in step (1), the reaction system, type and amount of initiator used in the polymerization reaction are relatively broad, and conventional olefin monomers can be used for free radical polymerization.

[0054] Preferably, the solvent used in the polymerization reaction can be selected from at least one of N,N-dimethylformamide (DMF), acetonitrile, toluene, xylene and dichloromethane, and more preferably N,N-dimethylformamide.

[0055] Preferably, the initiator used in the polymerization reaction can be selected from at least one of azobisisobutyronitrile, azobisisoheptanenitrile and benzoyl peroxide, and more preferably azobisisobutyronitrile. Preferably, the molar ratio of the initiator: (monomer A'+monomer B') is 1: (2-25).

[0056] According to the present invention, in step (1), the polymerization reaction is carried out in an oxygen-free and water-free environment. Preferably, the polymerization reaction conditions include: a temperature of 20-200° C. and a time of 0.5-48 hours.

[0057] According to the present invention, in step (1), on the basis of satisfying the above-mentioned molar ratio of monomer A':monomer B', preferably, the molar ratio of monomer A':monomer B' is 1:(1-2), so that the prepared gel polymer electrolyte has better interface stability.

[0058] According to the present invention, in step (2), the process and parameters used for the blending film are relatively broad, as long as the base polymer and the modified polymer can be blended to produce a uniform polymer film.

[0059] In some embodiments of the present invention, the blending film-making method comprises:

[0060] (2-1) mixing the base polymer, the modified polymer and a solvent to obtain a polymer solution;

[0061] (2-2) The polymer solution is subjected to a film-forming treatment to obtain the polymer film.

[0062] According to the present invention, in step (2-1), the solvent is a polar solvent, which can be selected from at least one of water, acetone, carbonate, N,N-dimethylformamide (DMF), N,N-dimethylacetamide (DMAc), dimethyl sulfoxide (DMSO), tetrahydrofuran (THF), and dioxane.

[0063] According to the present invention, in step (2-1), preferably, the mixing temperature can be 40-100° C., which is conducive to obtaining a better mixing effect.

[0064] According to the present invention, in step (2-2), the film forming treatment method may include casting, coating, papermaking, hot pressing, screen printing, freeze drying, electrospinning, phase inversion, impregnation, foaming, in-situ polymerization, Bellcore method, etc. In the specific implementation, the devices and operating conditions known in the art can be used, and the present invention does not make any special limitation on this.

[0065] According to the present invention, in step (2), the weight ratio of the base polymer to the modified polymer is 1:(0.01-9), which can make the prepared polymer film have a stable structure and excellent film-forming properties. Preferably, the weight ratio of the base polymer to the modified polymer is 1:(1-2).

[0066] According to the present invention, in step (2), the modified polymer is selected from at least one of polyolefins, polysulfonates, polycarbonates, polyacrylates, polyester terephthalates, polyethers, polyimides, polyacrylonitrile, nylon and cellulose, preferably at least one of polyolefins, polyacrylates and polyimides, more preferably polyolefins, such as polyvinylidene fluoride (PVDF).

[0067] According to the present invention, in step (3), the polymer film is immersed in the electrolyte salt solution to plasticize and swell the polymer film so that the polymer film fully absorbs the electrolyte salt solution to obtain a gel polymer electrolyte.

[0068] In the present invention, the type of electrolyte salt in the electrolyte salt solution is relatively broad, and conventional selections in the art can be used, including but not limited to at least one of zinc salts, lithium salts, sodium salts, potassium salts, calcium salts, magnesium salts and aluminum salts. For example, the electrolyte salt can be lithium hexafluorophosphate (LiPF6), lithium bistrifluoromethanesulfonyl imide (LiTFSI) or lithium bisfluorosulfonyl imide (LIFSI), etc.

[0069] In the present invention, the type of solvent in the electrolyte salt solution is relatively broad, and conventional choices in the art can be used, including but not limited to water, carbonates, ethers, ionic liquids, etc. Preferably, the concentration of the salt (the salt refers to a metal ion compound) in the electrolyte salt solution is 0.1-50 mol / L.

[0070] According to the present invention, in step (3), preferably, the conditions for plasticizing and swelling include: temperature of 10-40° C., and time of 1 min-24 h.

[0071] The third aspect of the present invention provides a gel polymer electrolyte prepared by the method described in the second aspect.

[0072] According to the present invention, the composition and performance of the gel polymer electrolyte prepared by the method described in the second aspect are the same as those of the gel polymer electrolyte described in the first aspect of the present invention, and will not be described in detail herein.

[0073] A fourth aspect of the present invention provides a battery comprising the gel polymer electrolyte described in the second or third aspect.

[0074] According to the present invention, the battery comprises a positive electrode, a negative electrode and an electrolyte, wherein the electrolyte is the gel polymer electrolyte described in the second aspect or the third aspect of the present invention. Compared with batteries using conventional electrolytes, under the same conditions, the battery provided by the present invention has more advantages in terms of cycle stability and safety.

[0075] The battery provided by the present invention includes but is not limited to semi- / full-solid-state lithium ion batteries, semi- / full-solid-state sodium ion batteries, semi- / full-solid-state lithium sulfur ion batteries, etc. According to some embodiments of the present invention, the use of the gel polymer electrolyte provided by the present invention in a lithium ion battery can make the ion battery have excellent cycle stability and long service life.

[0076] The present invention will be described in detail below by way of examples. In the following examples and comparative examples, unless otherwise specified, all are conventional methods; the reagents and materials, unless otherwise specified, can be obtained from commercial sources.

[0077] Example 1

[0078] (1) Dry a 100 mL Shrek bottle and a 50 mL single-mouth bottle at 110° C. for 30 min and cool them down; replace the nitrogen gas in the single-mouth bottle three times, add 20 mL of ultra-dry DMF into the single-mouth bottle, and bubble for 30 min; add azobisisobutyronitrile (AIBN) into the Shrek bottle, replace the nitrogen gas three times, transfer the bubbled DMF into the Shrek bottle, and then add monomer A' (methyl methacrylate) and monomer B' (acrylonitrile) into the Shrek bottle, where monomer A': monomer The molar ratio of monomer A' and monomer B' is 1:1; the molar ratio of AIBN: (monomer A' + monomer B') is 1:13; nitrogen gas is bubbled in the above reaction system for 30 minutes, and then the reaction is carried out at 80°C for 6 hours; after the reaction is completed, the reaction is cooled to room temperature, and the product system is added dropwise to deionized water to precipitate a white solid, and the white solid is dissolved in DMF at 70°C, and then the obtained solution is cooled, and the cooled solution is added dropwise to deionized water to precipitate a white solid, which is filtered and dried to obtain a matrix polymer;

[0079] The obtained matrix polymer was tested by infrared spectroscopy, and the results are shown in Figure 1 , Figure 1 It can be seen that at the wave number 2900cm -1 The -CH stretching vibration of -CH3 or -CH2 appears at the wave number 2244cm -1 -CN stretching vibration appears at wave number 1724cm -1 -C=O stretching vibration appears at wave number 1650-1500cm -1 There is no peak at , and no C=C double bond exists, indicating that methyl methacrylate monomer and acrylonitrile monomer are successfully polymerized to obtain the matrix polymer;

[0080] In the obtained matrix polymer, the structural unit Structural unit The molar ratio is 1:1;

[0081] (2-1) mixing the above-mentioned matrix polymer and polyvinylidene fluoride (PVDF) with a solvent (DMAc), and stirring at 50° C. for 4 hours to obtain a uniform and clear polymer solution; wherein the weight ratio of the matrix polymer to polyvinylidene fluoride is 1:1.5;

[0082] (2-2) Using a 500 μm coater, the polymer solution obtained in step (2-1) was uniformly coated on a clean and dry glass substrate; the glass substrate was first placed in deionized water at 80° C. for 5 min, then heated on a heating plate at 45° C. for 6 h, and then dried in a vacuum drying oven at 60° C. for 8 h, and the obtained white film was peeled off to obtain a polymer film (pore size of 0.5-2 μm, porosity of 51.2%);

[0083] (3) Soak the polymer film obtained in step (2-2) in 1 mol L -1 The solution was stirred for 10 h in a LiPF6 solution (the solvent was a mixture of ethylene carbonate, dimethyl carbonate and ethyl methyl carbonate in a weight ratio of 1:1:1) to obtain a gel polymer electrolyte (denoted as S1).

[0084] Example 2

[0085] (1) Dry a 100 mL Shrek bottle and a 50 mL single-mouth bottle at 110° C. for 30 min and cool them down; replace the nitrogen gas in the single-mouth bottle three times, add 20 mL of ultra-dry DMF into the single-mouth bottle, and bubble for 30 min; add azobisisobutyronitrile (AIBN) into the Shrek bottle, replace the nitrogen gas three times, transfer the bubbled DMF into the Shrek bottle, and then add monomer A' (methyl methacrylate) and monomer B' (acrylonitrile) into the Shrek bottle, where monomer A': monomer The molar ratio of monomer A' and monomer B' is 1:2; the molar ratio of AIBN: (monomer A' + monomer B') is 1:15; nitrogen is bubbled in the above reaction system for 30 minutes, and then reacted at 80°C for 6 hours; after the reaction is completed, it is cooled to room temperature, and the product system is added dropwise to deionized water to precipitate a white solid, and the white solid is dissolved in DMF at 70°C, and then the obtained solution is cooled, and the cooled solution is added dropwise to deionized water to precipitate a white solid, which is filtered and dried to obtain a matrix polymer;

[0086] In the obtained matrix polymer, the structural unit Structural unit The molar ratio is 1:2;

[0087] (2-1) mixing the above-mentioned matrix polymer and polyvinylidene fluoride with a solvent (DMAc), and stirring at 50° C. for 4 hours to obtain a uniform and clear polymer solution; wherein the weight ratio of the matrix polymer to polyvinylidene fluoride is 1:2;

[0088] (2-2) Using a 500 μm coater, the polymer solution obtained in step (2-1) was uniformly coated on a clean and dry glass substrate; the glass substrate was first placed in deionized water at 80° C. for 5 min, then heated on a heating plate at 45° C. for 6 h, and then dried in a vacuum drying oven at 60° C. for 8 h, and the obtained white film was peeled off to obtain a polymer film (pore size of 2-3 μm, porosity of 46%);

[0089] (3) Soak the polymer film obtained in step (2-2) in 1 mol L -1 The solution was stirred for 24 hours in a LiPF6 solution (the solvent was a mixture of ethylene carbonate, dimethyl carbonate and ethyl methyl carbonate in a weight ratio of 1:1:1) to obtain a gel polymer electrolyte (denoted as S2).

[0090] Example 3

[0091] (1) Dry a 100 mL Shrek bottle and a 50 mL single-mouth bottle at 110° C. for 30 min and cool by vacuuming; replace the nitrogen gas in the single-mouth bottle three times, add 20 mL of ultra-dry DMF into the single-mouth bottle, and bubble for 30 min; add azobisisobutyronitrile (AIBN) into the Shrek bottle, replace the nitrogen gas three times, transfer the bubbled DMF into the Shrek bottle, and then add monomer A' (methyl methacrylate) and monomer B' (methacrylonitrile) into the Shrek bottle, wherein monomer A': monomer B The molar ratio of ' is 1:0.05; the molar ratio of AIBN: (monomer A' + monomer B') is 1:10; nitrogen gas is bubbled in the above reaction system for 30 minutes, and then the reaction is carried out at 40°C for 24 hours; after the reaction is completed, the reaction is cooled to room temperature, and the product system is added dropwise to deionized water to precipitate a white solid, and the white solid is dissolved in DMF at 70°C, and then the obtained solution is cooled, and the cooled solution is added dropwise to deionized water to precipitate a white solid, which is filtered and dried to obtain a matrix polymer;

[0092] In the obtained matrix polymer, the structural unit Structural unit The molar ratio is 1:0.05;

[0093] (2-1) mixing the above-mentioned matrix polymer and polyvinylidene fluoride with a solvent (DMAc), and stirring at 50° C. for 4 hours to obtain a uniform and clear polymer solution; wherein the weight ratio of the matrix polymer to polyvinylidene fluoride is 1:0.01;

[0094] (2-2) Using a 500 μm coater, the polymer solution obtained in step (2-1) was uniformly coated on a clean and dry glass substrate; the glass substrate was first placed in deionized water at 80° C. for 5 min, then heated on a heating plate at 45° C. for 6 h, and then dried in a vacuum drying oven at 60° C. for 8 h, and the obtained white film was peeled off to obtain a polymer film (pore size of 0.1-1.5 μm, porosity of 20%);

[0095] (3) The polymer film obtained in step (2-2) was immersed in 1 mol L -1 The solution was stirred for 1 min in a LiPF6 solution (the solvent was a mixture of ethylene carbonate, dimethyl carbonate and ethyl methyl carbonate in a weight ratio of 1:1:1) to obtain a gel polymer electrolyte (denoted as S3).

[0096] Example 4

[0097] (1) Dry a 100 mL Shrek bottle and a 50 mL single-mouth bottle at 110° C. for 30 min and cool by vacuuming; replace the nitrogen gas in the single-mouth bottle three times, add 20 mL of ultra-dry DMF into the single-mouth bottle, and bubble for 30 min; add azobisisobutyronitrile (AIBN) into the Shrek bottle, replace the nitrogen gas three times, transfer the bubbled DMF into the Shrek bottle, and then add monomer A' (methyl methacrylate) and monomer B (methacrylonitrile) into the Shrek bottle, where monomer A': monomer The molar ratio of monomer A' and monomer B' is 1:28; the molar ratio of AIBN: (monomer A' + monomer B') is 1:9; nitrogen is bubbled in the above reaction system for 30 minutes, and then reacted at 100°C for 1 hour; after the reaction is completed, the reaction is cooled to room temperature, and the product system is added dropwise to deionized water to precipitate a white solid, and the white solid is dissolved in DMF at 70°C, and then the obtained solution is cooled, and the cooled solution is added dropwise to deionized water to precipitate a white solid, which is filtered and dried to obtain a matrix polymer;

[0098] In the obtained matrix polymer, the structural unit Structural unit The molar ratio is 1:28;

[0099] (2-1) mixing the above-mentioned matrix polymer and polyvinylidene fluoride with a solvent (DMAc), and stirring at 50° C. for 4 hours to obtain a uniform and clear polymer solution; wherein the weight ratio of the matrix polymer to polyvinylidene fluoride is 1:9;

[0100] (2-2) Using a 500 μm coating applicator, the polymer solution obtained in step (2-1) was uniformly coated on a clean and dry glass substrate; the glass substrate was first placed in deionized water at 80° C. for 5 min, then heated on a heating plate at 45° C. for 6 h, and then dried in a vacuum drying oven at 60° C. for 8 h, and the obtained white film was peeled off to obtain a polymer film (pore size of 0.5-2.3 μm, porosity of 21%);

[0101] (3) The polymer film obtained in step (2-2) was immersed in 1 mol L -1 The solution was stirred for 24 hours in a LiPF6 solution (the solvent was a mixture of ethylene carbonate: dimethyl carbonate: ethyl methyl carbonate in a weight ratio of 1:1:1) to obtain a gel polymer electrolyte (denoted as S4).

[0102] Example 5

[0103] (1) Dry a 100 mL Shrek bottle and a 50 mL single-mouth bottle at 110° C. for 30 min and cool by vacuuming; replace the nitrogen gas in the single-mouth bottle three times, add 20 mL of ultra-dry DMF into the single-mouth bottle, and bubble for 30 min; add azobisisobutyronitrile (AIBN) into the Shrek bottle, replace the nitrogen gas three times, transfer the bubbled DMF into the Shrek bottle, and then add monomer A' (ethyl methacrylate) and monomer B' (methacrylonitrile) into the Shrek bottle, where monomer A': monomer The molar ratio of monomer A' and monomer B' is 1:28; the molar ratio of AIBN: (monomer A' + monomer B') is 1:9; nitrogen is bubbled in the above reaction system for 30 minutes, and then reacted at 100°C for 1 hour; after the reaction is completed, the reaction is cooled to room temperature, and the product system is added dropwise to deionized water to precipitate a white solid, and the white solid is dissolved in DMF at 70°C, and then the obtained solution is cooled, and the cooled solution is added dropwise to deionized water to precipitate a white solid, which is filtered and dried to obtain a matrix polymer;

[0104] In the obtained matrix polymer, the structural unit Structural unit The molar ratio is 1:28;

[0105] (2-1) mixing the above-mentioned matrix polymer polyvinylidene fluoride with a solvent (DMAc), and stirring at 50° C. for 4 hours to obtain a uniform and clear polymer solution; wherein the weight ratio of the matrix polymer to polyvinylidene fluoride is 1:9;

[0106] (2-2) Using a 500 μm coater, the polymer solution obtained in step (2-1) was uniformly coated on a clean and dry glass substrate; the glass substrate was first placed in deionized water at 80° C. for 5 min, then heated on a heating plate at 45° C. for 6 h, and then dried in a vacuum drying oven at 60° C. for 8 h, and the obtained white film was peeled off to obtain a polymer film (pore size of 0.3-2.5 μm, porosity of 20%);

[0107] (3) Soak the polymer film obtained in step (2-2) in 1 mol L -1 The solution was stirred for 24 hours in a LiPF6 solution (the solvent was a mixture of ethylene carbonate, dimethyl carbonate and ethyl methyl carbonate in a weight ratio of 1:1:1) to obtain a gel polymer electrolyte (denoted as S5).

[0108] Example 6

[0109] (1) Dry a 100 mL Shrek bottle and a 50 mL single-mouth bottle at 110° C. for 30 min and cool by vacuuming; replace the nitrogen gas in the single-mouth bottle three times, add 20 mL of ultra-dry DMF into the single-mouth bottle, and bubble for 30 min; add azobisisobutyronitrile (AIBN) into the Shrek bottle, replace the nitrogen gas three times, transfer the bubbled DMF into the Shrek bottle, and then add monomer A' (methyl methacrylate) and monomer B' (acrylonitrile) into the Shrek bottle, wherein monomer A': monomer B The molar ratio of ' is 1:28; the molar ratio of AIBN: (monomer A' + monomer B') is 1:9; nitrogen is bubbled in the above reaction system for 30 minutes, and then reacted at 100°C for 1 hour; after the reaction is completed, it is cooled to room temperature, and the product system is added dropwise to deionized water to precipitate a white solid, and the white solid is dissolved in DMF at 70°C, and then the obtained solution is cooled, and the cooled solution is added dropwise to deionized water to precipitate a white solid, which is filtered and dried to obtain a matrix polymer;

[0110] In the obtained matrix polymer, the structural unit Structural unit The molar ratio is 1:28;

[0111] (2-1) mixing the above-mentioned matrix polymer and polyvinylidene fluoride with a solvent (DMAc), and stirring at 50° C. for 4 hours to obtain a uniform and clear polymer solution; wherein the weight ratio of the matrix polymer to polyvinylidene fluoride is 1:9;

[0112] (2-2) Using a 500 μm coater, the polymer solution obtained in step (2-1) was uniformly coated on a clean and dry glass substrate; the glass substrate was first placed in deionized water at 80° C. for 5 min, then heated on a heating plate at 45° C. for 6 h, and then dried in a vacuum drying oven at 60° C. for 8 h, and the obtained white film was peeled off to obtain a polymer film (pore size of 0.6-2.5 μm, porosity of 24%);

[0113] (3) The polymer film obtained in step (2-2) was immersed in 1 mol L -1 The solution was stirred for 24 hours in a LiPF6 solution (the solvent was a mixture of ethylene carbonate, dimethyl carbonate and ethyl methyl carbonate in a weight ratio of 1:1:1) to obtain a gel polymer electrolyte (denoted as S6).

[0114] Example 7

[0115] (1) Dry a 100 mL Shrek bottle and a 50 mL single-mouth bottle at 110° C. for 30 min and cool them down; replace the nitrogen in the single-mouth bottle three times, add 20 mL of ultra-dry DMF into the single-mouth bottle, and bubble for 30 min; add azobisisobutyronitrile (AIBN) into the Shrek bottle, replace the nitrogen three times, transfer the bubbled DMF into the Shrek bottle, and then add monomer A' (methyl methacrylate) and monomer B' (methacrylonitrile) into the Shrek bottle, where monomer A': monomer The molar ratio of monomer A' and monomer B' is 1:28; the molar ratio of AIBN: (monomer A' + monomer B') is 1:9; nitrogen is bubbled in the above reaction system for 30 minutes, and then reacted at 100°C for 1 hour; after the reaction is completed, the reaction is cooled to room temperature, and the product system is added dropwise to deionized water to precipitate a white solid, and the white solid is dissolved in DMF at 70°C, and then the obtained solution is cooled, and the cooled solution is added dropwise to deionized water to precipitate a white solid, which is filtered and dried to obtain a matrix polymer;

[0116] In the obtained matrix polymer, the structural unit Structural unit The molar ratio is 1:28;

[0117] (2-1) mixing the above-mentioned matrix polymer and polycarbonate with a solvent (DMAc), and stirring at 50° C. for 4 hours to obtain a uniform and clear polymer solution; wherein the weight ratio of the matrix polymer to the polycarbonate is 1:9;

[0118] (2-2) Using a 500 μm coater, the polymer solution obtained in step (2-1) was uniformly coated on a clean and dry glass substrate; the glass substrate was first placed in deionized water at 80° C. for 5 min, then heated on a heating plate at 45° C. for 6 h, and then dried in a vacuum drying oven at 60° C. for 8 h, and the obtained white film was peeled off to obtain a polymer film (pore size of 0.8-2.3 μm, porosity of 27%);

[0119] (3) Soak the polymer film obtained in step (2-2) in 1 mol L -1 The solution was stirred for 24 hours in a LiPF6 solution (the solvent was a mixture of ethylene carbonate, dimethyl carbonate and ethyl methyl carbonate in a weight ratio of 1:1:1) to obtain a gel polymer electrolyte (denoted as S7).

[0120] Example 8

[0121] (1) Dry a 100 mL Shrek bottle and a 50 mL single-mouth bottle at 110° C. for 30 min and cool them down; replace the nitrogen in the single-mouth bottle three times, add 20 mL of ultra-dry DMF into the single-mouth bottle, and bubble for 30 min; add azobisisobutyronitrile (AIBN) into the Shrek bottle, replace the nitrogen three times, transfer the bubbled DMF into the Shrek bottle, and then add monomer A' (methyl methacrylate) and monomer B' (methacrylonitrile) into the Shrek bottle, where monomer A': monomer The molar ratio of monomer A' and monomer B' is 1:28; the molar ratio of AIBN: (monomer A' + monomer B') is 1:9; nitrogen is bubbled in the above reaction system for 30 minutes, and then reacted at 100°C for 1 hour; after the reaction is completed, the reaction is cooled to room temperature, and the product system is added dropwise to deionized water to precipitate a white solid, and the white solid is dissolved in DMF at 70°C, and then the obtained solution is cooled, and the cooled solution is added dropwise to deionized water to precipitate a white solid, which is filtered and dried to obtain a matrix polymer;

[0122] In the obtained matrix polymer, the structural unit Structural unit The molar ratio is 1:28;

[0123] (2-1) mixing the above-mentioned matrix polymer and polyvinylidene fluoride with a solvent (DMAc), and stirring at 50° C. for 4 hours to obtain a uniform and clear polymer solution; wherein the weight ratio of the matrix polymer to polyvinylidene fluoride is 1:5;

[0124] (2-2) Using a 500 μm coater, the polymer solution obtained in step (2-1) was uniformly coated on a clean and dry glass substrate; the glass substrate was first placed in deionized water at 80° C. for 5 min, then heated on a heating plate at 45° C. for 6 h, and then dried in a vacuum drying oven at 60° C. for 8 h, and the obtained white film was peeled off to obtain a polymer film (pore size of 0.9-1.5 μm, porosity of 25%);

[0125] (3) The polymer film obtained in step (2-2) was immersed in 1 mol L -1 The solution was stirred for 24 hours in a LiPF6 solution (the solvent was a mixture of ethylene carbonate, dimethyl carbonate and ethyl methyl carbonate in a weight ratio of 1:1:1) to obtain a gel polymer electrolyte (denoted as S8).

[0126] Comparative Example 1

[0127] The method of Example 4 is followed, except that in step (1), the molar ratio of monomer A':monomer B' is 1:30, so that the structural unit in the obtained matrix polymer Structural unit The molar ratio of is 1:30. The other steps and conditions are the same as those in Example 4 to obtain a gel polymer electrolyte (denoted as D1).

[0128] Comparative Example 2

[0129] The method of Example 4 is followed, except that in step (1), monomer A' is replaced by an equimolar amount of amino acrylate The other steps and conditions were the same as those in Example 4 to obtain a gel polymer electrolyte (denoted as D2).

[0130] Comparative Example 3

[0131] The method of Example 4 is followed, except that polyvinylidene fluoride is not added in step (2-1), that is, no modified polymer is used. The other steps and conditions are the same as those of Example 4, to obtain a gel polymer electrolyte (denoted as D3).

[0132] Test Case

[0133] Cyclic stability test

[0134] The gel polymer electrolytes S1-S8 and D1-D3 prepared in the above-mentioned Examples 1-8 and Comparative Examples 1-3 were used to assemble lithium-ion batteries (respectively B1-B8 and DB1-DB3) with the positive electrode and the negative electrode, respectively, wherein the active material in the positive electrode was LiFePO4 and a lithium metal negative electrode was used. The coulombic efficiency of the above-mentioned batteries B1-B8 and DB1-DB3 was tested at 25°C under 3C charging and 3C discharging cycles for 1500 cycles. The results are shown in Table 1.

[0135] Table 1

[0136] Test subjects Coulomb efficiency (1500 cycles) B1 99.06% B2 98.67% B3 92.61% B4 93.65% B5 91.67% B6 93.52% B7 93.34% B8 92.69% DB1 85.43% DB2 82.67% DB3 80.51%

[0137] As can be seen from Table 1, the gel polymer electrolytes S1-S8 provided by the present invention have excellent interface stability, can effectively resist the corrosion and damage of the electrolyte, have good compatibility with the battery electrodes, effectively reduce the risk of battery short circuit, and make the battery have excellent cycle stability, long service life and good safety. Under the above test conditions, the coulomb efficiency of batteries B1-B8 can be greater than 90% after 1500 cycles, and can reach up to 99.06%, while D1-D3 does not meet the composition of the gel polymer electrolyte of the present invention, and the cycle stability of batteries DB1-DB3 is not as good as that of batteries B1-B8.

[0138] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A gel polymer electrolyte comprising: A polymer body, and an electrolyte salt solution impregnated in the polymer body; the polymer body contains a base polymer and a modified polymer; Wherein, the base polymer contains a structural unit A represented by formula (I) and a structural unit B represented by formula (II); In formula (I), R1 and R2 are each independently selected from hydrogen or a C1-C3 alkyl group; R3 and R4 are each independently selected from a C1-C3 alkyl group; In formula (II), R5, R6, and R7 are each independently selected from hydrogen or a C1-C3 alkyl group; The molar ratio of structural unit A:structural unit B is 1:(0.05-28).

2. The gel polymer electrolyte according to claim 1, wherein The molar ratio of structural unit A:structural unit B is 1:(1-2).

3. The gel polymer electrolyte according to claim 1 or 2, wherein: The weight ratio of the base polymer to the modified polymer is 1:(0.01-9), preferably 1:(1-2).

4. The gel polymer electrolyte according to any one of claims 1 to 3, wherein: The modified polymer is selected from at least one of polyolefins, polysulfonates, polycarbonates, polyacrylates, polyterephthalates, polyethers, polyimides, polyacrylonitrile, nylon and cellulose; And / or, the electrolyte salt is selected from at least one of zinc salt, lithium salt, sodium salt, potassium salt, calcium salt, magnesium salt and aluminum salt.

5. A method for preparing a gel polymer electrolyte, comprising: (1) polymerizing monomer A' and monomer B' to obtain a matrix polymer; (2) blending the base polymer and the modified polymer to form a film to obtain a polymer film; (3) plasticizing and swelling the polymer film with an electrolyte salt solution to obtain a gel polymer electrolyte; Wherein, the monomer A' has a structure shown in formula (III), and the monomer B' has a structural unit shown in formula (IV); In formula (III), R1' and R2' are each independently selected from hydrogen or a C1-C3 alkyl group; R3' and R4' are each independently selected from a C1-C3 alkyl group; In formula (IV), R5', R6', and R7' are each independently selected from hydrogen or a C1-C3 alkyl group; The molar ratio of the monomer A':monomer B' is 1:(0.05-28).

6. The method according to claim 5, wherein: In step (1), the polymerization reaction conditions include: temperature of 20-200° C., time of 0.5-48 h; and / or, in step (2), the weight ratio of the base polymer to the modified polymer is 1:(0.01-9), preferably 1:(1-2); And / or, in step (3), the conditions for plasticizing and swelling include: temperature of 10-40° C. and time of 1 min-24 h.

7. The method according to claim 5 or 6, wherein: The modified polymer is selected from at least one of polyolefins, polysulfonates, polycarbonates, polyacrylates, polyester terephthalates, polyethers, polyimides, polyacrylonitrile, nylon and cellulose, preferably at least one of polyolefins, polyacrylates and polyimides.

8. The method according to any one of claims 5 to 7, wherein: The electrolyte salt is selected from at least one of zinc salts, lithium salts, sodium salts, potassium salts, calcium salts, magnesium salts and aluminum salts.

9. A gel polymer electrolyte prepared by the method according to any one of claims 5 to 7.

10. A battery comprising the gel polymer electrolyte according to any one of claims 1 to 4 and 9.